The Potential of Autologous Platelet-Rich Plasma Gel for Diabetic Foot Ulcer Care Among Older Adults: A Systematic Review and Meta-Analysis - Platini H; Adammayanti KA; Maulana S; Putri PMK; Layuk WG; Lele JAJMN; Haroen H; Pratiwi SH; Musthofa F; Mago A (Therapeutics and Clinical Risk Management, 2024)
Hesti Platini,1 Keyzha Amartya Adammayanti,2 Sidik Maulana,3 Putu Moradha Kharisma Putri,2 Welly Grivin Layuk,2 Juan Alessandro Jeremis Maruli Nura Lele,2 Hartiah Haroen,4 Sri Hartati Pratiwi,1 Faizal Musthofa,5,6 Arpit Mago7 1Department of Medical-Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Clinical Clerkship Program, Faculty of Medicine, Universitas Kristen Indonesia (UKI), UKI Hospital East Jakarta, Special Capital Region, Indonesia; 3Master of Nursing Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 4Department of Community Health Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 5Nursing Internship Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 6West Sapphire Medical-Surgical Ward, Santosa Bandung Central, Bandung, West Java, Indonesia; 7Department of Clinical Medicine, Jawaharlal Nehru Medical College, Belagavi, IndiaCorrespondence: Hesti Platini, Department of Medical-Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, West Java, 40132, Indonesia, Tel +62 822-1671-8363, Email hesti13001@unpad.ac.idIntroduction: Poorly controlled diabetes mellitus can lead to the development of diabetic foot ulcers (DFU), which is a frequent complication in patients. However, several diabetes management guidelines for older adults do not mention the occurrence of DFUs. Nowadays, Autologous Platelet-Rich Gel (APG) is being used for treating diabetic ulcers. APG is an innovative platelet-derived product with many advantages, such as being low-cost, easy to produce, and readily available materials. Additionally, it does not lead to any rejection reaction.Objective: This study aims to assess the safety and efficacy of APG as a novel treatment of DFU compared with standard treatment in older adult patients.Methods: Randomized Controlled Trials (RCTs) were searched using PubMed, Cochrane, Google Scholar, Wiley, and PlosOne. The keywords have been arranged using the Boolean operator, including autologous platelet-rich gel, DFU, and elderly. The data was screened by inclusion and exclusion criteria. The final inclusion study was analyzed and synthesized by tabulation, clusterization, contextual and thematic approach, and assessed for risk of bias using ROB 2.0. Meta-analysis was conducted by using Review Manager 5.4 and the Mantel Haenszel method.Results: Eight RCTs with 598 patients were eligible for the present analysis. Compared with standard care/conventional treatment, APG could significantly improve the healing wound in patients with diabetic foot ulcers (Relative risk (RR) 1.32, 95% confidence interval (CI) 1.22– 1.57, p < 0.0001), shortened the healing time (Mean difference [MD] − 16.97 days (95% CI: − 32.64 to − 1.29; p < 0.00001), shortened the length of hospital stay (MD= − 20.11, 95% CI: − 38.02, − 2.20; p = 0.03), and amputation rate (MD= 0.36, 95% CI: 0.16, 0.84; p = 0.02).Conclusion: APG treatment can better treat DFU in terms of duration of healing, wound healing, length of hospital stay, and amputation prevention than the standard treatment.Keywords: autologous platelet-rich plasma gel, diabetic foot ulcers, older adult